Ionic liquid-modified polyimide membranes with in-situ-grown polydopamine for separation of oil–water emulsions. (September 2022) - Qi, Peng; Jia, Hongge; Wang, Qingji; Su, Guiming; Xu, Shuangping; Zhang, Mingyu; Qu, Yanqing; Pei, Fuying
Leakage of oily industrial waste is not only a serious environmental and ecological hazard but also poses a significant health risk to people. Membrane separation, which is cost-effective and efficient, is one of the best solutions for reducing pollution discharge through oil–water separation. In this study, polydopamine (PDA) was incorporated into electrostatically spun ionic liquid-capped polyimide (IL-PI) membranes through an in situ growth method; the membranes exhibited the strong adsorption properties of PDA. The polyimide fibers were hydrophilically modified with an IL, which contains several hydrophilic groups, and PDA. Adjusting the polymerization time resulted in the formation of a composite membrane, which could effectively separate oil–water emulsions. Scanning electron microscopy analysis showed that with an increase in the PDA coating time, the PDA content in and on the surface of the composite membrane fibers significantly increased. In addition, the surface contact angle of the membrane decreased from 72.87° to 12.06° with the addition of the PDA coating, while the wettability was significantly improved. The PDA-modified fibrous membranes showed good separation of the emulsified oil–water mixtures. The maximum membrane flux and separation efficiency achieved was 280 L·m −2 ·h −1 and >99%, respectively. After 10 repeated cycles, the separation efficiency was maintained at >92%. This approach can be used for the design of future wastewater treatment solutions.